Development, validation and evaluation of pro-dips to improve quality of patient care for total knee replacement patients - Muhamad, Hartini (2022)
Discharge planning is the process of individual treatment plans for patients before leaving the hospital to improve the quality of patient care, reduce the length of patient stay in the hospital, improve patient self-care knowledge and increase patient satisfaction. This study aims to develop, validate and evaluate the effectiveness of discharge planning in patients undergoing total knee replacement. It is a mixed-method study consisting of three phases using a multi-phase mixed-method design. In Phase 1, the DOES Model and Programmatic Discharge Planning System (Pro-DiPS) framework were formed sequentially from highlight searches, surveys using questionnaires of 96 patients undergoing total knee replacement, in-depth interviews with 10 patients, and 25 professional staff. This was followed by an opinion poll and validation process from 25 experts from various disciplines conducted using the Delphi technique, and a review process by experts using the focus group discussion technique. In Phase 2, the Pro-DiPS Module validation process from the implementation of the workshop aims to train the professional health officers involved in the study and for the evaluation of the teaching made. After the workshop, a preliminary study was conducted on three patients who will undergo total knee replacement surgery to assess the feasibility of Pro-DiPS in patient care to identify deficiencies and improve Pro-DiPS before the pilot study is conducted. Finally, in phase 3, 16 patients were in the intervention group and 13 patients were in the control group. Pro-DiPS is implemented as a system in patient care in the intervention group while the control group receives care with the existing system. The effectiveness of this intervention is assessed by measuring the knee function and patient satisfaction, organizational efficiency in terms of outgoing and long-term stay in the hospital, and feedback from health professionals and related patients in terms of the level of feasibility and feasibility of Pro-DiPS. The results of Phase 1 show that Pro-DiPS was found to be valid with 100% expert agreement through four rounds of Delphi technique and 100% agreement from expert review process using focused group discussion techniques. In Phase 2, Pro-DiPS was validated with patient and caregiver feedback rates in the implementation of workshops on average 4 and 5 which is at an excellent rate there is only 1 feedback at a rate of 3 which is moderate. Written feedback from three participants also showed satisfaction with the system carried out. In Phase 3, the effect of the intervention although there was no significant difference (p>0.05) showed an increase in the mean score of the implementation of Pro-DiPS on patient outcomes and the satisfaction of professional health staff. Anyhow, patient satisfaction, the result shows a significant difference (p=0.029) and the intervention group has a higher median score of 9.00(IQR=2.00) compared to the control group 8.00(IQR=3.75). In conclusion, studies at this hospital suggest that developing and implementing a structured system (Pro-DiPS) helps to improve patient care systematically and organize. As this is the first pilot study in Malaysia to focus on discharge planning led by nurses, more evidence-based studies need to be conducted in the future to further enhance the results of this potential intervention.